1995
DOI: 10.1091/mbc.6.9.1197
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of the CDK inhibitor p27 between different cyclin.CDK complexes in the mouse fibroblast cell cycle and in cells arrested with lovastatin or ultraviolet irradiation.

Abstract: The cyclin-dependent kinase (CDK) inhibitor p27 binds and inhibits the kinase activity of several CDKs. Here we report an analysis of the behavior and partners of p27 in Swiss 3T3 mouse fibroblasts during normal mitotic cell cycle progression, as well as in cells arrested at different stages in the cycle by growth factor deprivation, lovastatin treatment, or ultraviolet (UV) irradiation. We found that the level of p27 is elevated in cells arrested in G0 by growth factor deprivation or contact inhibition. In G0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
249
2

Year Published

1998
1998
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(267 citation statements)
references
References 53 publications
16
249
2
Order By: Relevance
“…Similar mechanisms of CDK inhibition by p27 [KIP1] were previously reported earlier for growth inhibition mediated by TGFb and lovastatin (Chen et al, 1996;Hall et al, 1995;Peters, 1994;Poon et al, 1995). In these situations p27 [KIP1] redistribution was attributed (i) to the inhibition of cyclin D1 expression in cells arrested by lovastatin (Poon et al, 1995) and (ii) to the synthesis of the p15 [INK4B] inhibitor in the case of TGFb (Hannon and Beach, 1994;Reynisdottir et al, 1995). In 7TD1 cells this last possibility can be ruled out since we demonstrated that p15 [INK4B] and p16 [INK4A] are not stimulated by DMSO (data not shown).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Similar mechanisms of CDK inhibition by p27 [KIP1] were previously reported earlier for growth inhibition mediated by TGFb and lovastatin (Chen et al, 1996;Hall et al, 1995;Peters, 1994;Poon et al, 1995). In these situations p27 [KIP1] redistribution was attributed (i) to the inhibition of cyclin D1 expression in cells arrested by lovastatin (Poon et al, 1995) and (ii) to the synthesis of the p15 [INK4B] inhibitor in the case of TGFb (Hannon and Beach, 1994;Reynisdottir et al, 1995). In 7TD1 cells this last possibility can be ruled out since we demonstrated that p15 [INK4B] and p16 [INK4A] are not stimulated by DMSO (data not shown).…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, since in 7TD1 cells cyclin D2/CDK4 is principally associated with p27 [KIP1] the DMSO-dependent cyclin D2 inhibition provides free p27 [KIP1] molecules that can associate with cyclin E/CDK2 complexes. Similar mechanisms of CDK inhibition by p27 [KIP1] were previously reported earlier for growth inhibition mediated by TGFb and lovastatin (Chen et al, 1996;Hall et al, 1995;Peters, 1994;Poon et al, 1995). In these situations p27 [KIP1] redistribution was attributed (i) to the inhibition of cyclin D1 expression in cells arrested by lovastatin (Poon et al, 1995) and (ii) to the synthesis of the p15 [INK4B] inhibitor in the case of TGFb (Hannon and Beach, 1994;Reynisdottir et al, 1995).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…One possibility is that cyclin D1 functions by activating Cdk4 or Cdk6 or sequestering Cdk inhibitors (Poon et al, 1995), p21 and p27, which have been strongly linked to apoptosis when expressed at the wrong time in the cell cycle (Duttaroy et al, 1997;Katayose et al, 1997;Wang et al, 1997). The most widely recognized function of cyclin D-dependent kinases is phosphorylation of pRb which disrupts association of pRb with E2F family proteins (Sherr and Roberts, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of c-Myc in REF/Myc/4E clones was veri®ed to rule out the possibility that any new phenotype observed was due to loss of c-Myc expression. For immunoblot analysis of D cyclins, 40 mg of cytoplasmic extract prepared using a NP-40 lysis bu er (Poon et al, 1995) was subjected to SDS ± PAGE (12%) under reducing conditions, and blotted onto nitrocellulose. The blot was proved using primary antibodies against cyclins D1, D2, and D3 (Santa Cruz Biotechnologies, Inc., Santa Cruz, CA, USA; 1 : 200), appropriate horseradish peroxidase labeled secondary antibodies, and visualized by ECL.…”
Section: Immunoblot Analysismentioning
confidence: 99%